2016
DOI: 10.3389/fcimb.2015.00098
|View full text |Cite
|
Sign up to set email alerts
|

Smooth to Rough Dissociation in Brucella: The Missing Link to Virulence

Abstract: Dissociation encompasses changes in a series of phenotypes: colony and cell morphology, inmunological and biochemical reactions and virulence. The concept is generally associated to the in vitro transition between smooth (S) and rough (R) colonies, a phenotypic observation in Gram-negative bacteria commonly made since the beginning of microbiology as a science. It is also well known that the loss of the O-polysaccharide, the most external lipopolysaccharide (LPS) moiety, triggers the change in the colony pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 64 publications
0
30
0
1
Order By: Relevance
“…We discovered 14 such synthetic lethal genes in B. abortus ( Figure 6B and C) that have all been previously reported to play a role in O-polysaccharide synthesis (10,(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68); mutations in this gene set result in a rough phenotype in Brucella melitensis (58). It is well established that B. ovis is a rough strain that lacks LPS Opolysaccharide (28,58,69,70). Indeed, many of the O-polysaccharide genes that are synthetically lethal with eipA in B. abortus are frame-shifted, carry nonsense mutations, or are absent from the genome of B. ovis ( Figure 6C) (28,71).…”
Section: Eipa Is Essential In Brucella Ovis and Is Synthetically Lethmentioning
confidence: 80%
“…We discovered 14 such synthetic lethal genes in B. abortus ( Figure 6B and C) that have all been previously reported to play a role in O-polysaccharide synthesis (10,(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68); mutations in this gene set result in a rough phenotype in Brucella melitensis (58). It is well established that B. ovis is a rough strain that lacks LPS Opolysaccharide (28,58,69,70). Indeed, many of the O-polysaccharide genes that are synthetically lethal with eipA in B. abortus are frame-shifted, carry nonsense mutations, or are absent from the genome of B. ovis ( Figure 6C) (28,71).…”
Section: Eipa Is Essential In Brucella Ovis and Is Synthetically Lethmentioning
confidence: 80%
“…B and C) that have been previously reported to play a role in O‐polysaccharide synthesis (Cloeckaert et al ., ; Ugalde et al ., ; Guzman‐Verri et al ., ; Monreal et al ., ; Manterola et al ., ; Cardoso et al ., ; Lamontagne et al ., ; Gonzalez et al ., ; Mancilla et al ., ; Zhang et al ., ; Tian et al ., ; Dabral et al ., ; Salvador‐Bescos et al ., ); mutations in this gene set result in a rough phenotype in Brucella melitensis (Gonzalez et al ., ). It is well established that B. ovis is a stably rough strain that lacks LPS O‐polysaccharide (Gonzalez et al ., ; Tsolis et al ., ; Soler‐Llorens et al ., ; Mancilla, ). Indeed, many of the O‐polysaccharide genes that are synthetically lethal with eipA in B. abortus are frame‐shifted, carry nonsense mutations, or are absent from the genome of B. ovis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Brucella , this phenomenon had been reported and was of great importance in basic and vaccine researches [ 34 ]. The phenotypic change of Brucella under natural conditions mainly existed in two ways: inserting fragments into genes and deletion of genes related to LPS synthesis [ 16 ]. In addition, studies had shown that changes in the expression levels of LPS-related genes also caused changes in the phenotype of Brucella [ 35 ].…”
Section: Discussionmentioning
confidence: 99%